ANALISIS PENYERAPAN TENAGA KERJA PADA SEKTOR INDUSTRI PENGOLAHAN SERTA KONTRIBUSNYA TERHADAP PRODUK DOMESTIK REGIONAL BRUTO KOTA DUMAI TAHUN 2010-2016 - Sri Hartati br Barus; Lapeti Sari; Toti Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This case is purposed on employee absorbent in manufacture industrysectors of Dumai Municipality in the other hand, this observation also analyze theamountcontribution of gross domestic regional product in Dumai Municipality. Inanalyzingpurpose , this observation used secondary data of time series from 2010 up to 2016 that resourced from BPS East Java Province. The analyze method thatused iselasticity work opportunity analyzing and methods of economic growth. Result of thereseach the elasticity method of labor absortion is inelastic absorbent, howeverthe average of employee absorbent elasticity is kind of inelastic of 0,79 %, andonly 2013-2014 years of elasticity is kind elastic of 3,80 %, while other sectors thecharacter of inelastic. The manufacture industry sector’s contribution to Dumai Municipality GDP the highest is in 2016 amounted to the lowest 53,88 %then is the year 2012 wich amounted to 49,29% and the average contribution was51,82%Keyword : Employee, manufacture industry sectors, GDP Dumai Municipality